An adaptive sliding mode–based fault-tolerant control design for half-vehicle active suspensions using T–S fuzzy approach. (17th January 2020) - Pang, Hui; Shang, Yuting; Yang, Junjie
This study proposes an improved adaptive sliding mode–based fault-tolerant control design for the improvement of dynamics performances of half-vehicle active suspensions with parametric uncertainties and actuator faults in the context of external road disturbances. To cope with the model establishment of the vehicle active suspensions, the T–S fuzzy approach and system augmentation technology are used to construct the T–S representation of the faulty augmented system, and a new adaptive law is, therefore, designed to achieve the accurate online estimation of the actuator gain and drift faults, which facilitates the desirable fault-tolerant controller design. Moreover, the proposed adaptive sliding mode–based fault-tolerant controller is synthesized, and the system stability analysis is further conducted in premise of the Lyapunov stability theory. Finally, a numerical simulation is provided to illustrate the effectiveness and robustness of the proposed controller.